A specific genetic marker for the discrimination of native Bulgarian honey bees (Apis mellifera rodopica): Duplication of coI gene fragment. Issue 3 (27th May 2017) - Radoslavov, Georgi; Hristov, Peter; Shumkova, Rositsa; Mitkov, Ivan; Sirakova, Daniela; Bouga, Maria
Abstract : In this study, we present for the first time SNPs analysis of a coI mitochondrial DNA (mtDNA) g ene segment of the local Rhodopa Mountain honey bee, A. m. rodopica, that is well investigated, based on morpho-ethological and biochemical studies. The analysis was performed on adult honey bee workers that were sampled from 29 colonies that are under the control of the Bulgarian National Beekeeping Association. Our data are compared with analogous studies obtained from other A. mellifera subspecies, and we describe a specific characteristic duplication of the coI gene for the Rhodopes honey bee that can be applied as a genetic marker to discriminate the local Bulgarian honey bees and to support the related conservation activities.